Thermal treatment enhances the resisting exercise fatigue effect of Phyllanthus emblica L.: novel evidence from tannin conversion in vitro, metabolomics, and gut microbiota community analysis - Dingkun Zhang; Xuan Deng; Mengqi Li; Min Qiu; Yifan Zhang; Gefei Li; Yurou Jiang; Peng Tan; Sanhu Fan; Youde Zheng; Junzhi Lin; Li Han; et al. (BMC, 2023)
Abstract Polyphenols are the main component of Phyllanthus emblica (PE). However, polyphenols are so easy to transform that it is unknown that how drying methods driven by heating affect the anti-fatigue effect of PE. This manuscript investigated the effects of five drying methods on the chemical composition transformation and anti-fatigue of PE, and discussed the action mechanism. The results suggested that the anti-fatigue effect of PE with hot-air-dried at 100 °C was the best, which was as 1.63 times as that with freeze-drying. Ellagic acid (EA) may be a key component of PE in anti-fatigue, and its mechanism of action may be related to regulating intestinal microbiota, protecting mitochondria, and regulating energy metabolism. This study first revealed the thermal transformation of polyphenols in PE, found the most effective strategy for enhancing the anti-fatigue function, and explores its action mechanism.